A novel transgenic rabbit model with reduced repolarization reserve: long QT syndrome caused by a dominant‐negative mutation of the KCNE1 gene. (19th May 2016) - Major, Péter; Baczkó, István; Hiripi, László; Odening, Katja E.; Juhász, Viktor; Kohajda, Zsófia; Horváth, András; Seprényi, György; Kovács, Mária; Virág, László; Jost, Norbert; Prorok, János; et al.
Abstract : Background and purpose: The reliable assessment of proarrhythmic risk of compounds under development remains an elusive goal. Current safety guidelines focus on the effects of blocking the KCNH2 /HERG ion channel‐in tissues and animals with intact repolarization. Novel models with better predictive value are needed that more closely reflect the conditions in patients with cardiac remodelling and reduced repolarization reserve. Experimental Approach: We have developed a model for the long QT syndrome type‐5 in rabbits (LQT5 ) with cardiac‐specific overexpression of a mutant (G52R) KCNE1 β‐subunit of the channel that carries the slow delayed‐rectifier K + ‐current (IKs ). ECG parameters, including short‐term variability of the QT interval (STVQT ), a biomarker for proarrhythmic risk, and arrhythmia development were recorded. In vivo, arrhythmia susceptibility was evaluated by i.v. administration of the IKr blocker dofetilide. K + currents were measured with the patch‐clamp technique. Key Results: Patch‐clamp studies in ventricular myocytes isolated from LQT5 rabbits revealed accelerated IKs and IKr deactivation kinetics. At baseline, LQT5 animals exhibited slightly but significantly prolonged heart‐rate corrected QT index (QTi) and increased STVQT . Dofetilide provoked Torsade‐de‐Pointes arrhythmia in a greater proportion of LQT5 rabbits, paralleled by a further increase in STVQT . Conclusion and Implications: We have created a novel transgenic LQT5 rabbit model with increased susceptibility to drug‐induced arrhythmias that may represent a useful model for testing proarrhythmic potential and for investigations of the mechanisms underlying arrhythmias and sudden cardiac death due to repolarization disturbances.